Pekan Lightning Detection System (PLDS) and Data Validation with Lightning TNBR - Wan Ismail, Ibrahim; Mohd Riduwan, Ghazali; Lailatul Niza, Muhammad; Suliana, Ab Ghani; Nurul Azlina, Abdul Rahman; Norhasliza, Mohd Hatta (2013)
Lightning Location System (LLS) based on MDF and TOA technique has been installed and setup in Universiti Malaysia Pahang, Pekan for lightning warning and monitoring system. The two important aspects of the performance of LLS are the location accuracy and detection efficiency (DE). In this paper, the real-time data include the time of lightning strokes, their location and an estimate of the peak current has been compared with Lightning Location Network (LDN) owned by TNBR Malaysia to validate the DE of the system.